Size Versus Intensity of Majority and Minority Consensus to a Persuasive Message: From the Source of Influence to Its Recipients - Stamos Papastamou; Gerasimos Prodromitis (International Review of Social Psychology, 2019)
This study examines the effects of the evaluation of the majority or minority consensus attributed to a message on the influence the latter can exert, in a between subjects factorial design 2 (consensus status: 'majority' vs 'minority') × 3 (orientation of the consensus evaluation: 'non-evaluation, size evaluation, intensity evaluation'). Its innovative aspect consists in its explicit focus on participants’ evaluation of the intensity and size of the support allegedly attributed to the message of the source. The main results show that with regard to direct influence: a) in a non-evaluation condition, the majority consensus tends to be more influential than the minority consensus, whereas in the intensity evaluation condition, the minority consensus is the most influential; b) the impact of minority consensus increases when its intensity is evaluated compared to the non-evaluation condition. Regarding the indirect influence: a) the non-evaluation of the majority consensus favors its impact compared to that obtained by the minority consensus, but b) the evaluation conditions make this difference fade away, by decreasing the influence of majority consensus while increasing that of minority consensus. We discuss the significance and the limitations of these results, which seem to put aside the barriers usually encountered by the sources of influence (diminished direct influence for the minority and restricted indirect influence for the majority).